Semen Quality Traits of Seven Strain of Chickens Raised in the Humid Tropics - Peters, S.O.; Shoyebo, O.D.; Ilori, B.M.; Ozoje, M.O.; Ikeobi, C.O.N.; Adebambo, O.A. (International Journal of Poultry Science, 2008)
This research was conducted to investigate variation in semen quality traits of seven chicken strains. A total of 42 cocks belonging to 7 sire strains comprising of 3 Nigerian indigenous (Naked-neck, Frizzle and Normal feathered) cocks, 3 Exotic cocks (Nera Black, White Leghorn and Giriraja) and an improved indigenous crossbred (Alpha) cock developed at the Poultry Breeding Unit of the Teaching and Research Farm, College of Animal Science and Livestock Production, University of Agriculture, Alabata Road, Abeokuta, Ogun State between March, 2002 and April, 2003. Strain effect significantly affected semen volume (P < 0.05), sperm concentration (P < 0.001), motility (P < 0.05), colour (P < 0.01), active (P < 0.05) and sluggish (P < 0.05) spermatozoa but not on semen pH (P > 0.05). The White Leghorn had the highest semen volume, while the Naked neck had the least. The observed semen volume ranged from 0.37 ± 0.02 to 0.73 ± 0.01 ml. Naked neck birds had the highest value for sperm concentration followed by the Normal feathered strain, Nera black, White Leghorn, Alpha, Frizzle feather and Giriraja with corresponding values of 4.21 ± 1.45 x 109/ml, 4.05 ± 0.65 x 109/ml, 3.89 ± 0.83 x 109/ml, 3.53 ± 1.00 x 109/ml, 3.45 ± 0.46 x 109/ml, 3.40 ± 0.31 x 109/ml respectively. Naked neck had the highest value for motile spermatozoa while the Giriraja had the least value. The Pearson correlation coefficients between semen volume and other quality traits were generally low with positive values ranging from 0.01-0.35 between semen volume and percentage sluggish spermatozoa and semen pH and sperm motility respectively. It is concluded that large genetic variation existed in semen quantity and quality traits in cocks used for the study and that indigenous cocks had comparable results with the exotics and can therefore be included in A.I for genetic improvement as contributors of rare genes.